ANALISIS RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PERUSAHAAN PERBANKAN DAN LEMBAGA KEUANGAN LAIN YANG GO PUBLIK DI BURSA EFEK INDONESIA PADA PERIODE 2004-2006 - Ernie Riswandari (Universitas Bunda Mulia, 2017)
The objective of this study is to define the return on assets (ROA) and return on equity (ROE) price to book value (PBV) banking companies and other financial institutions that have gone public Indonesian stock exchange (IDX) and see how much ability in ROA and ROE variables in explaining variables PBV banking companies and other financial institutions that have gone public BEI. Based on the results of hypothesis testing, companies Banking and Other Financial Institutions company obtained results showed that there was a significant relationship and there that do not have a significant relationship, it is because the sample used in different years and different economic conditions. So the author concludes that the information ROA and ROE is not the only factor considered by an investor or a less dominant role in influencing the decision to buy or sell stocks. In other words, there are many other relevant information that can be used by investors in the IDX in economic decisions. Kata kunci: Return on Asset (ROA),Return On Equity (ROE), Price to Book Value( PBV)